PjBL Model assisted by Smartphone Sensors to Improve Critical Thinking Skills of Prospective Science Teachers - Prasetyo Listiaji; Risti Ayu Widianingrum; Anggita Ayu Ivanda Saputri; Nor Farahwahidah Abdul Rahman (Universitas Muhammadiyah Surakarta, 2022)
This research aims to analyze the improvement of the critical thinking skills of prospective science teachers after the implementation of smartphone-assisted PjBL and analyze the responses of prospective science tea-chers to the applied learning model. The research used an experimental model with a Nonequivalent Control Group Design. The research subjects were 2nd semester Science Education Program students in 2 classes of basic physics courses (experimental and control) as prospective science teachers. Data collection methods were test techniques for measuring critical thinking skills and questionnaire methods for determining stu-dent responses. Data analysis methods ware N-Gain analysis, independent sample t-test, and qualitative descriptive. The results showed a high increase in critical thinking skills in the experimental class, as indi-cated by an N-Gain score of 0.71. The results of the hypothesis test also showed that there was a significant difference between the post-test scores of the experimental and control classes. The PjBL model assisted by smartphone sensors also received a very good response from prospective science teacher students. The PjBL model assisted by smartphone sensors can be implemented to improve the critical thinking skills of pros-pective science teachers and can also be a reference for innovative learning models that align with the de-mands of technology-based 21st-century learning.